Accurate capacity factor calculation of waste-to-energy power plants based on availability analysis and design/off-design performance. (1st December 2020) - Naderi, Shayan; Banifateme, Mohsen; Pourali, Omid; Behbahaninia, Ali; MacGill, Iain; Pignatta, Gloria
Abstract: The aim of this study is to obtain more realistic estimations of the achievable capacity factor and availability of waste-to-energy power plants to better understand their economics, and hence facilitate appropriate deployment. Towards this aim, we introduce Markov analysis and off-design considerations into the calculation of plant performance. Parameters such as increasing failure rates as a result of aging, infant mortality failures, and overhauls are all taken into account with our approach. Meanwhile, the effect of failures on such plant's operating mode is evaluated, and Stodola's cone law is applied to calculate the actual power generation in off-design mode. A system divided into three main sub-components, two steam generation blocks and a power generation block, each of which has its own failure and repair rates, is proposed for this study. The state-space diagram of the proposed system is constructed and simplified, and the transient differential equations governing the state-space diagram are solved numerically. Having obtained the availability of the system and off-design performance, the capacity factor is calculated and compared with actual field data. Also, a new availability-based formulation is presented to obtain the net present value of the cash flow. Results show that by using a time-varying failure rate, the availability of the power plant declines about 23% over 20 years, a significant difference to estimated availability if a constant failure rate was assumed. Our findings highlight that the present price of electricity, $0.057 per kWh, for generation from the plant is insufficient to encourage investment in this technology in Iran at present, and greater deployment will require some form of policy intervention. Highlights: Markov analysis is conducted to calculate the availability of a WtE power plant. Stodola's cone law is utilized to simulate the plant's off-design performance. A new methodology is presented to calculate a more accurate capacity factor. The availability is calculated using constant and variable failure rates.